Evaluation of exposure of auto painters to organic solvents in the city of Bogota (2015)
Introduction: Painters of automobiles are exposed to pure and mixed solvents that have been associated with neurological effects and carcinogenic mutations. Objective: To characterize the health and work conditions of individuals who are occupationally exposed to organic solvents used in sheet metal and auto body shops in Bogota. Materials and methods: Descriptive, cross-sectional study that characterizes the health and work conditions of individuals exposed to organic solvents in sheet metal and auto body shops in Bogota. A group exposed to the solvents was compared to an unexposed group. Air concentrations of benzene, toluene and xylene (BTX) were determined, individual questionnaires were administered and phenylmercapturic, hippuric and ortho- and para-methylhippuric acids were measured in urine. The results of the measurements and the questionnaires were correlated to determine the exposure panorama. Results: For the three BTX metabolites, statistically significant differences (p less than 0.001) were found between the population exposed to the solvents and the unexposed population. For the exposed population, positive correlations were found between toluene in air and hippuric acid in urine (rho=0.82) and between xylene in air and o-methylhippuric acid in urine (rho=0.76). Hippuric acid values exceeded permissible levels in 11 workers and p-methylhippuric acid exceeded permissible levels in 8 workers. None of the phenylmercapturic values exceeded the limit.Conclusion: Auto painters are exposed to high levels of organic solvents at the workplace and do not have adequate industrial health and safety conditions to perform their jobs.